Study on current–voltage characteristics of OLEDs using Alq3 as the electron transport layer - Cuong, Nguyen Kien (VNU Journal of Science: Mathematics - Physics; Vol 27 No 3, 2011)
Abstract. This paper describes changes in current-voltage (I-V) characteristic of  an organic light-emitting device (OLED) stacked as a multilayer of ITO/MEH-PPV/Alq 3 /Al. The ordered, stacked ITO/MEH-PPV/Alq 3 /Al multi-layers were fabricated by spin-coating and thermal vacuum evaporation methods. First, dissolved MEH-PPV solution was spin-coated on ITO-electrodes that had been covered on a glass-slide.  Subsequently, an Alq 3 layer was evaporated thermally on the MEH-PPV-coated layer. Finally, an Al-electrode was evaporated also on the electron transport layer. UV-vis absorption and photoluminescent characterization of the MEH-PPV and Alq 3 layer as well as their surface images were performed. All spectra obtained revealed the MEH-PPV and Alq 3 were deposited as given structure. The I-V characteristics show the present of the Alq 3 -electron transport layer deposited between the MEH-PPV emissive layer and Al-cathode could enhance current-voltage characteristic reducing the threshold voltage and turn-on voltage. Keywords: UV-vis absorption, photoluminescence, electron transport layer, current-voltage characteristics.